Collaboration Between Biomedical and Complementary and Alternative Care Providers: Barriers and Pathways. (December 2017) - van der Watt, Alberta S. J.; Nortje, Gareth; Kola, Lola; Appiah-Poku, John; Othieno, Caleb; Harris, Benjamin; Oladeji, Bibilola D.; Esan, Oluyomi; Makanjuola, Victor; Price, LeShawndra N.; Seedat, Soraya; Gureje, Oye
We examined the scope of collaborative care for persons with mental illness as implemented by traditional healers, faith healers, and biomedical care providers. We conducted semistructured focus group discussions in Ghana, Kenya, and Nigeria with traditional healers, faith healers, biomedical care providers, patients, and their caregivers. Transcribed data were thematically analyzed. A barrier to collaboration was distrust, influenced by factionalism, charlatanism, perceptions of superiority, limited roles, and responsibilities. Pathways to better collaboration were education, formal policy recognition and regulation, and acceptance of mutual responsibility. This study provides a novel cross-national insight into the perspectives of collaboration from four stakeholder groups. Collaboration was viewed as a means to reach their own goals, rooted in a deep sense of distrust and superiority. In the absence of openness, understanding, and respect for each other, efficient collaboration remains remote. The strongest foundation for mutual collaboration is a shared sense of responsibility for patient well-being.